Identifying Structural Breaks in Cointegrated VAR Models - Håvard Hungnes (Statistics Norway, Research Department, 2005)
The paper describes a procedure for decomposing the deterministic terms in cointegrated VAR models into growth rate parameters and cointegration mean parameters. These parameters express long-run properties of the model. For example, the growth rate parameters tell us how much to expect (unconditionally) the variables in the system to grow from one period to the next, representing the underlying (steady state) growth in the variables. The procedure can be used for analysing structural breaks when the deterministic terms include shift dummies and broken trends. By decomposing the coefficients into interpretable components, different types of structural breaks can be identified. Both shifts in intercepts and shifts in growth rates, or combinations of these, can be tested for. The ability to distinguish between different types of structural breaks makes the procedure superior compared to alternative procedures. Furthermore, the procedure utilizes the information more efficiently than alternative procedures. Finally, interpretable coefficients of different types of structural breaks can be identified.
Keywords: C32; C51; C52; 330; Johansen procedure; cointegrated VAR; structural breaks; growth rates; cointegration mean levels.